Preparation of preferentially (111)-oriented Mg2Si thin films on (001)Al2O3 and (100)CaF2 substrates and their thermoelectric properties. (3rd March 2017) - Kurokawa, Mao; Uehara, Mutsuo; Ichinose, Daichi; Shimizu, Takao; Akiyama, Kensuke; Matsushima, Masaaki; Uchida, Hiroshi; Kimura, Yoshisato; Funakubo, Hiroshi
Abstract: Mg2 Si thin films were deposited at 320 °C on (001)Al2 O3 and (100)CaF2 substrates by radio-frequency magnetron sputtering. Both films showed a preferential (111) out-of-plane orientation with an in-plane random orientation irrespective of post-heat treatment. Mg2 Si films on (001)Al2 O3 substrates were under in-plane tensile strain, while those on (100)CaF2 substrates were under in-plane compressive strain both before and after heat treatment. Heat-treated films showed p-type conduction up to 500 °C. Their electrical conductivity and Seebeck coefficient were almost independent of the kind of substrate within the limit of the present study, from 0.22% compressive strain to 0.34% tensile strain at room temperature.